Agenda For Studying The Causes Of The 44-Day Nagorno-Karabakh War Within The Framework Of Neoclassical Realism: A Methodological Introduction - Soghomonyan, Menua (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
This article aims to contribute to the agenda of the study of the causes of the 44-day Nagorno-Karabakh war based on theses of theories of International Relations and their conceptions. The article is part of a planned comprehensive study, and it tries to prove that when exploring the roots of the 44-day war within the framework of political Realism of International Relations theory, the most relevant approach is Neoclassical Realism. The study of the causes of the 44-day war through the lenses of theories of International Relations is a more systemic approach to the object of inquiry, which directs the thinking of a scholar to a framework of more comprehensive and logically interrelated variables. It is worth mentioning that this article does not concentrate on the reasons for the 44-day war per se. The article argues that though Structural Realism (among IR realist theories) is very important to focus on the structure and dynamics of the international system (both global and South-Caucasian regional levels), it does not overwhelmingly address the reasons for the 44-day war. Those reasons should be looked for in the foreign policy strategies of the actors in the South Caucasus, as well as in the perception of the regional structure and dynamics by the Armenian elites and their ability to mobilize resources according to those perceptions. The variables are part of the ontology of neoclassical realism.
Keywords: Theories of International Relations